2021
DOI: 10.1002/ana.26004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Light Chain Levels in the Intensive Care Unit: Comparison between Severely Ill Patients with and without Coronavirus Disease 2019

Abstract: There is emerging evidence for multifarious neurological manifestations of coronavirus disease 2019 (COVID‐19), but little is known regarding whether they reflect structural damage to the nervous system. Serum neurofilament light chain (sNfL) is a specific biomarker of neuronal injury. We measured sNfL concentrations of 29 critically ill COVID‐19 patients, 10 critically ill non–COVID‐19 patients, and 259 healthy controls. After adjusting for neurological comorbidities and age, sNfL concentrations were higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 20 publications
(25 reference statements)
7
73
2
Order By: Relevance
“…We concluded that changes in these CNS damage biomarkers were more pronounced in hospitalized patients compared to non-hospitalized individuals and healthy controls [8] . Results confirming this have subsequently been reported in other studies [ 9 , 10 ]. In addition, in the search for useful biomarkers to predict COVID-19 outcomes, cytokine growth differentiation factor 15 (GDF-15) was recently proposed as a biomarker of general disease severity and unfavourable outcomes [11] .…”
Section: Introductionsupporting
confidence: 92%
“…We concluded that changes in these CNS damage biomarkers were more pronounced in hospitalized patients compared to non-hospitalized individuals and healthy controls [8] . Results confirming this have subsequently been reported in other studies [ 9 , 10 ]. In addition, in the search for useful biomarkers to predict COVID-19 outcomes, cytokine growth differentiation factor 15 (GDF-15) was recently proposed as a biomarker of general disease severity and unfavourable outcomes [11] .…”
Section: Introductionsupporting
confidence: 92%
“…Levels of serum Nfl have been found to be elevated in subjects with a number of neurological degenerative diseases (12), (13), (14), (15), as well as those with acute conditions such as hypoxic brain injury (16), cardiac and related surgeries (17), (18), and traumatic brain injury (19). Recent studies have found increased levels of Nfl in COVID-19 patients (20), (21),(22) but the effects of concomitant systemic inflammatory disease such as cardiac disease or diabetes on neuronal injury as measured by NfL in COVID-19 patients has not been previously reported. In the present study we examined the relationship between levels of serum Nfl in COVID-19 positive ICU patients and the presence of cardiovascular disease, diabetes, and acute neurological complications.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers re ecting nervous system damage in COVID-19 patients A prospective study showed that total Tau, GFAP, and NFL protein levels in cerebrospinal uid were elevated in 63%, 37%, and 16% of patients, respectively, and NFL protein was associated with disease severity, duration of intensive care and level of consciousness [110] .Multiple studies on COVID-19 patients with ischemic stroke have shown that the neutrophil-lymphocyte ratio (NLR) is increased in 90% of the patients [111] , CRP is increased in over 90% of the patients [112] , and serum ferritin is also increased [113] , in which serum ferritin can also predict the degree of nerve injury in patients with acute ischemic stroke [114] .There was a signi cant correlation between the decrease of interleukin-6 level and the improvement of olfaction and taste function in COVID-19 patients [115] .Elevated serum nerve lament light chain (SNFL) levels in critically ill patients with COVID-19 are closely associated with poor prognosis [116] .…”
Section: Evidence Of Neurological Damage In Covid-19 Patientsmentioning
confidence: 99%